Activation by odorants of a multistate cation channel from olfactory cilia. - Labarca, P (1988)
Single-channel records were obtained after fusion of ciliary membranes from the olfactory epithelium of Rana catesbeiana to planar lipid bilayers, and odorant-activated cation-selective channels were identified. In addition, a 190-pS potassium-selective channel and a 40-pS cation-selective channel were found in a 0.2 M salt-containing buffer. Odorant-sensitive channels were directly and reversibly activated by nanomolar concentrations of the bell pepper odorant 3-isobutyl-2-methoxypyrazine and the citrus odorant 3,7,-dimethyl-2,6-octadienenitrile. These channels display burst kinetics, multiple conductance levels between 35 and 420 pS, and open times in the millisecond range. With increasing concentrations of odorant, the probability of populating the higher conductance levels increases. These results show that direct activation of channels by odorants may mediate excitation of the olfactory receptor cell.